2013
DOI: 10.4172/2161-1041.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants: The Missing Key to Improved Therapeutic Intervention in Smith-Lemli-Opitz Syndrome

Abstract: Smith-Lemli-Opitz Syndrome (SLOS) is a recessive hereditary disease caused by an enzymatic defect in the biosynthesis of cholesterol. To date, the therapeutic standard of care for this disease has been cholesterol supplementation therapy. However, the efficacy of this treatment is extremely variable and, in many if not most cases, is poor. Results of studies using animal models of SLOS have suggested that cholesterol deficiencyand/or the aberrant accumulation of the immediate precursor of cholesterol (7-dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…In accordance with the results of Tint et al (7), we previously reported that both the initial value of serum cholesterol level and the cholesterol/7DHC ratio had an important prognostic value in the severity, development and life expectancy of SLOS children (8). To date, routine therapy has been cholesterol supplementation in SLOS; while combined cholesterol-simvastatin therapy (9,10) or cholesterol-antioxidant treatment might also be effective in SLOS patients (11). However, as it was recently reviewed, simvastatin is not recommended for SLOS treatment due to its potential side effects (12).…”
Section: Introductionsupporting
confidence: 75%
“…In accordance with the results of Tint et al (7), we previously reported that both the initial value of serum cholesterol level and the cholesterol/7DHC ratio had an important prognostic value in the severity, development and life expectancy of SLOS children (8). To date, routine therapy has been cholesterol supplementation in SLOS; while combined cholesterol-simvastatin therapy (9,10) or cholesterol-antioxidant treatment might also be effective in SLOS patients (11). However, as it was recently reviewed, simvastatin is not recommended for SLOS treatment due to its potential side effects (12).…”
Section: Introductionsupporting
confidence: 75%
“…The resulting modifications in the sterol pattern impair the chemical and biological properties of cellular membranes. Indeed, the substitution of 7-DHC for cholesterol into cell membranes worsens membrane fluidity, lipid raft stability, and localization of membrane proteins [88].…”
Section: Huntington's Diseasementioning
confidence: 99%
“…In fact, cytotoxic, 7DHC-derived oxysterols may be key players underlying the pathobiology of SLOS [32,33]. Hence, in addition to cholesterol supplementation or interventions that target the aberrant formation and accumulation of 7DHC, which to date have not been shown to be reliably or substantially efficacious in minimizing SLOS-associated phenotypic or functional abnormalities (for a review, see [1,34]), an improved therapeutic approach might include antioxidants (in addition to cholesterol) to suppress the formation of 7DHC-derived oxysterols [32,33,35]. Such an approach is currently ongoing in a limited clinical trial at Children's Hospital Denver, and the initial results are showing promise (R. Braverman and E. Elias, personal communication).…”
Section: Membrane Science and Technologymentioning
confidence: 99%